SOSIALISASI PENERAPAN SAK EMKM PADA PENYUSUNAN LAPORAN KEUANGAN UMKM YANG TERDAFTAR PADA DINAS KETENAGAKERJAAN, KOPERASI, DAN USAHA KECIL MENENGAH KABUPATEN MAJALENGKA - Eva Fauziah Ahmad; rizal sukma aliyudin (CV. Multi Kreasi Media, 2022)
Usaha Mikro, Kecil dan Menengah (UMKM) is an important part of the national economy and development. However, this big role is also balanced with the obstacles it has, namely the UMKM actors still have difficulties in preparing financial reports. Seeing the importance of applying accounting for UMKM and this is also adjusted by taking into account the characteristics of UMKM transactions, the Dewan Standar Akuntansi Keuangan (DSAK) under the auspices of the Indonesian Institute of Accountants (IAI) has issued SAK-EMKM (Micro, Small and Medium Financial Accounting Standards) and since 1 January 2018. This community service aims to create and provide an understanding of financial statements in order to have quality information in accordance with applicable standards. It is hoped that this service will increase the understanding of MSME actors on the application of SAK EMKM in the preparation of financial reports.